Pelvic inflammatory disease and the risk factors - Vanamala, V. G.; Pakyanadhan, Sushil; Rachel, Aruna; P., Sudeep Abraham (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Pelvic inflammatory disease is one of the most common gynecological disorders of women. It is a clinical condition where in the endometrial, fallopian tubes and the adjacent pelvic structures are infected due to the ascending infection from the lower genital tract such as vagina and cervix through the uterine cavity leading to severe morbidity. Methods: 150 non-pregnant women who came in with clinical symptoms suggestive of Pelvic inflammatory disease and diagnosed as acute pelvic infection or PID were included in the study. Demographic details such as age, weight, height, parity, socio-economic status, education levels etc were noted. Results: 54% of them belonged to 26-30 years age group, followed by 19.3% of women between 20-25 years. 35.3% of the patients were illiterate followed by primary school education in 29.3%. 74% of the patients belonged to the lower class while 24.7% were from the middle class. Condoms were the most common contraceptive method used in 32% of the cases, while 27.3% of the patients used intrauterine devices. Conclusions: Proper education must be given regarding the hazards of early marriages lack of hygiene, and to abstain from multiple partners, to the women especially those from the lower socioeconomic strata.